2008
DOI: 10.1160/th07-11-0684
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of antithrombin administration in the acute phase of burn injury

Abstract: all 10 cities including the rural areas of the province of Kerman. All data were finally analyzed by SPSS software (version 11.5). Results On the basis of recorded statistical analysis, the mortality cases of human rabies in the province of Kerman during one decade was 10 persons (eight males and two females). One-half of them (50%) were bitten by dogs and the others (50%) by foxes. Among the reported deaths, 40% were from Kahnooj county (Jiroft region). The reported data indicated that 21,546 persons were bit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 36 publications
0
41
0
Order By: Relevance
“…Pharmacokinetics of bolus vs continual infusion of phAT revealed that continual infusion consumed less drug over time and sustained fewer unintentional decreases in plasma once the steady state was reached; this also provided a cost benefit for the patient [33] . Lavrientieva et al [34] published a prospective, randomized study of 31 severely burned patients comparing phATtreated patients with controls. AT administration was started from the 1 st post-burn day and continued for the next 3 d [34] .…”
Section: Recombinant Atmentioning
confidence: 99%
See 4 more Smart Citations
“…Pharmacokinetics of bolus vs continual infusion of phAT revealed that continual infusion consumed less drug over time and sustained fewer unintentional decreases in plasma once the steady state was reached; this also provided a cost benefit for the patient [33] . Lavrientieva et al [34] published a prospective, randomized study of 31 severely burned patients comparing phATtreated patients with controls. AT administration was started from the 1 st post-burn day and continued for the next 3 d [34] .…”
Section: Recombinant Atmentioning
confidence: 99%
“…Lavrientieva et al [34] published a prospective, randomized study of 31 severely burned patients comparing phATtreated patients with controls. AT administration was started from the 1 st post-burn day and continued for the next 3 d [34] . The AT dose was titrated to the target value of plasma AT activity > 150% [34] .…”
Section: Recombinant Atmentioning
confidence: 99%
See 3 more Smart Citations